Twenty-Three Years of Declining Lithium Use: Analysis of a Pharmacoepidemiological Dataset from German-Speaking Countries - Greil, Waldemar; de Bardeci, Mateo; Nievergelt, Nadja; Toto, Sermin; Grohmann, Renate; Seifert, Johanna; Schoretsanitis, Georgios (Pharmacopsychiatry, 2024)
Introduction Pharmacoepidemiological data suggest that lithium prescriptions for bipolar disorder are gradually decreasing, with less attention having been paid to other indications.Methods We examined lithium prescriptions between 1994 and 2017 in data provided by the Drug Safety in Psychiatry Program AMSP, including psychiatric hospitals in Germany, Austria and Switzerland. We compared lithium use for different diagnoses before and after 2001 and in three periods (T1: 1994–2001, T2: 2002–2009, and T3: 2010–2017).Results In a total of 158,384 adult inpatients (54% female, mean age 47.4±17.0 years), we observed a statistically significant decrease in lithium prescriptions between 1994–2000 and 2001–2017 in patients with schizophrenia spectrum disorder from 7.7% to 5.1% and in patients with affective disorders from 16.8% to 9.6%. Decreases in use were also observed for diagnostic subgroups: schizoaffective disorder (ICD-10 F25: 27.8% to 17.4%), bipolar disorder (F31: 41.3% to 31%), depressive episode (F32: 8.1% to 3.4%), recurrent depression (F33: 17.9% to 7.5%, all: p<0.001) and emotionally unstable (borderline) personality disorder (6.3% to 3.9%, p=0.01). The results in T1 vs. T2 vs. T3 were for F25: 26.7% vs. 18.2% vs. 16.2%, F32: 7.7% vs. 4.2% vs. 2.7%, F33: 17.2% vs. 8.6% vs. 6.6% and for F31: 40.8% vs. 31.7% vs 30.0%, i. e. there was no further decrease for lithium use in bipolar disorder after 2002. Lithium’s main psychotropic co-medications were quetiapine (21.1%), lorazepam (20.6%), and olanzapine (15.2%).Discussion In inpatients, the use of lithium has decreased in patients with bipolar disorder and also with various other psychiatric diagnoses.
Keywords: lithium; pharmacoepidemiology; bipolar disorders; polypharmacy; psychopharmacology